Grand Triebel-Lizorkin-Morrey spaces - Ho Kwok-Pun (Demonstratio Mathematica)
This article studies the Triebel-Lizorkin-type spaces built on grand Morrey spaces on Euclidean spaces. We establish a number of characterizations on the grand Triebel-Lizorkin-Morrey spaces such as the Peetre maximal function characterizations, the Lusin area function characterizations, and the gλ∗{g}_{λ }^{* } function characterizations. The boundedness of the Fourier multipliers on the grand Triebel-Lizorkin-Morrey spaces is also obtained.